Initial EPM Post-Graduation Outcomes Report - Marie Francois:::::: (2023)
Part I of this Embedded Peer Mentor (EPM) Post-Graduation Outcomes project investigating what has been happening with EPMs since they left CI suggests the EPM experience has a strong impact on post-graduation futures. The focus of the current research is on the two-thirds of the EPMs who have graduated since the program began in 2011 (64 of 95) who supported students in Learning Communities (LCs) and Living-Learning Communities (LLCs) between academic years 2011-12 and 2022-23.